2008
DOI: 10.1016/j.virol.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus polymerase suppresses translation of pregenomic RNA via a mechanism involving its interaction with 5′ stem–loop structure

Abstract: The pregenomic RNA (pgRNA) of hepadnaviruses serves a dual role: as mRNA for the core (C) and polymerase (P) synthesis and as an RNA template for viral genome replication. A question arises as to how these two roles are regulated. We hypothesized that the P protein could suppress translation of the pgRNA via its interaction with 5' stem-loop structure (epsilon or encapsidation signal). Consistent with the hypothesis, we observed up-regulation of the C protein level in the absence of the P protein expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 29 publications
2
57
0
Order By: Relevance
“…The HBV Pol expression construct, from which HBV Pol with three copies of the Flag epitope at N terminus is expressed, was described previously (19). The pgRNA expression plasmid was derived from the pCMV-HBV/30 plasmid, the wild-type HBV replicon construct, from which both the C (core) open reading frame and the (Pol) open reading frame were inactivated by an introduction of a stop codon and a frameshift mutation, respectively, as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The HBV Pol expression construct, from which HBV Pol with three copies of the Flag epitope at N terminus is expressed, was described previously (19). The pgRNA expression plasmid was derived from the pCMV-HBV/30 plasmid, the wild-type HBV replicon construct, from which both the C (core) open reading frame and the (Pol) open reading frame were inactivated by an introduction of a stop codon and a frameshift mutation, respectively, as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…It is not clear, however, whether and how the dual functions of the pgRNA are coordinated. Recently, we demonstrated that HBV Pol directs genome replication by suppressing the translation of the pgRNA (19). Therefore, we speculated that the translation suppression of the pgRNA could precede encapsidation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…HepG2 cells were grown in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10 % fetal bovine serum (Gibco-BRL) and 10 mg gentamicin ml 21 at 37 uC in 5 % CO 2 and passaged every third day. Cells were transfected using polyethylenimine (PEI; 25 kDa; Sigma-Aldrich) as described previously (Ryu et al, 2008). Briefly, cells were plated at 40-50 % confluency.…”
Section: Methodsmentioning
confidence: 99%